2017
DOI: 10.3748/wjg.v23.i23.4252
|View full text |Cite
|
Sign up to set email alerts
|

Pancreas preserving distal duodenectomy: A versatile operation for a range of infra-papillary pathologies

Abstract: AIMTo investigate the range of pathologies treated by pancreas preserving distal duodenectomy (PPDD) and present the outcome of follow-up.METHODSNeoplastic lesions of the duodenum are treated conventionally by pancreaticoduodenectomy. Lesions distal to the major papilla may be suitable for a pancreas-preserving distal duodenectomy, potentially reducing morbidity and mortality. We present our experience with this procedure. Selective intraoperative duodenoscopy assessed the relationship of the papilla to the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
2
6
2
1
Order By: Relevance
“…DGE after PSDD in the current study occurred in 42% of patients, which was higher than previous reports for PD (12–46%) [37–41] and PSDD (0–16%) [20, 25, 42]. The cause of DGE in PSDD was reported to be ischemia or edema of the stump or gastric‐duodenal atony due to reduced circulating levels of motilin secreted from the duodenum, which is associated with the interdigestive migrating motor complex [13, 37, 43, 44].…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…DGE after PSDD in the current study occurred in 42% of patients, which was higher than previous reports for PD (12–46%) [37–41] and PSDD (0–16%) [20, 25, 42]. The cause of DGE in PSDD was reported to be ischemia or edema of the stump or gastric‐duodenal atony due to reduced circulating levels of motilin secreted from the duodenum, which is associated with the interdigestive migrating motor complex [13, 37, 43, 44].…”
Section: Discussioncontrasting
confidence: 81%
“…However, we should carefully determine the surgical indications of this procedure because it is still challenging for tumors located on the 4th part or distal side of the 3rd part of the duodenum. DGE after PSDD in the current study occurred in 42% of patients, which was higher than previous reports for PD (12-46%) [37][38][39][40][41] and PSDD (0-16%) [20,25,42]. The cause of DGE in PSDD was reported to be ischemia or edema of the stump or gastric-duodenal atony due to reduced circulating levels of motilin secreted from the duodenum, which is associated with the interdigestive migrating motor complex [13,37,43,44].…”
Section: Discussioncontrasting
confidence: 73%
“…Primary adenocarcinoma of the fourth segment of the duodenum and the proximal jejunum can also be safely resected with limited (distal) duodenal resection, especially when the tumor is small and the small bowel mesentery and the head of the pancreas/uncinate process are not involved. Many studies comparing pancreaticoduodenectomy with limited duodenal resection have reported equivalent long-term outcome and overall survival with less morbidity [ 20 , 21 ]. A recent propensity-matched analysis of 2,487 patients comparing radical resection with partial resection for duodenal adenocarcinoma concluded that adjuvant therapy in addition to surgery improved survival regardless of the type of surgery and played a significant role in survival [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Insbesondere bei der FAP führt dieses Verfahren zu einer Entfernung möglicher weiterer Prädilektionsstellen. Die pankreaserhaltende Duodenektomie stellt entsprechend bei gutartigen Befunden das Pendant zur Pankreaskopfresektion dar und wird in den Händen erfahrener Pankreaschirurgen als gleichwertig hinsichtlich der Komplikationsrate bewertet 23 , 31 . In Analogie zur transduodenalen Papillektomie wird auch die pankreaserhaltende Duodenektomie von einigen Autoren für das Früh- bzw.…”
Section: Chirurgische Therapieunclassified